Teacher-student relationships : crossing into the emotional, physical, and sexual realms - Zarra, Ernest J., 1955- (Rowman and Littlefield Education, 2013)
Teachers and teenage students are becoming involved in inappropriate sexual relationships, often leading to devastation and arrest. Teacher-Student Relationships: Crossing into the Emotional, Physical, and Sexual Realms addresses the reasons these relationships develop, considers the roles of modern technology in the development, and offers solutions from within the profession.